2007
DOI: 10.1111/j.1365-2265.2007.02803.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in TSH but not in free T4 concentrations or TPO antibodies during pregnancy

Abstract: The increase in TSH and decrease in free T4 values during pregnancy correspond to previous reported studies. Pregnant Dutch women had consistently higher TSH values than the ethnic group, but corresponding free T4 levels and TPO-Ab did not differ between these ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 20 publications
3
44
2
2
Order By: Relevance
“…The latter possibility would indicate real differences in the setpoint of the HPT axis between our subjects. Indeed ethnic differences in ambient TSH values but not in FT 4 values suggest an effect of race (17,18), and slightly lower TSH values have been observed in carriers of the Asp727Glu polymorphism in the TSH receptor gene occurring in about 20% of a Caucasian population (19). The low prevalence of this TSH receptor polymorphism does not favour possibility iii) in our (mostly Caucasian) subjects.…”
Section: Discussionmentioning
confidence: 68%
“…The latter possibility would indicate real differences in the setpoint of the HPT axis between our subjects. Indeed ethnic differences in ambient TSH values but not in FT 4 values suggest an effect of race (17,18), and slightly lower TSH values have been observed in carriers of the Asp727Glu polymorphism in the TSH receptor gene occurring in about 20% of a Caucasian population (19). The low prevalence of this TSH receptor polymorphism does not favour possibility iii) in our (mostly Caucasian) subjects.…”
Section: Discussionmentioning
confidence: 68%
“…Black and Asian women have TSH values that are on average 0.4 mIU/L lower than in white women; these differences persist during pregnancy (21,22). Pregnant women of Moroccan, Turkish, or Surinamese descent residing in The Netherlands, have TSH values 0.2-0.3 mIU/L lower than Dutch women throughout pregnancy (23). TSH ranges vary slightly depending on differences between methods of analysis (24).…”
mentioning
confidence: 99%
“…13,20 Black and Asian women have TSH values that are on average 0.4 mIU/ L lower than in white women; these differences persist during pregnancy. 20,21,22 Pregnant women of Moroccan, Turkish, or Surinamese descent residing in the Netherlands, have TSH values 0.2-0.3 mIU/L lower than Dutch women throughout pregnancy. 21 Kumar and associates found that mean T 4 levels began to rise from 16.45 pmol/L in the first trimester to 16.58 pmol/L in the second trimester and then decreased in the third trimester to 15.99 pmol/L, they also reported that mean TSH level also rise progressively through the three trimesters of pregnancy from 1.20 mlU/ L in the first trimester to 2.12 mIU/L in the second trimester and further to 3.30 mIU/L in the third trimester of pregnancy, which was not consistent with this study findings.…”
Section: Discussionmentioning
confidence: 99%